ANALISIS PEMUNGUTAN PPh FINAL ATAS PENGALIHAN HAK ATAS TANAH DAN/ATAU BANGUNAN (PADA STUDI KASUS PERUSAHAAN DEVELOPER PT. INDOJAYA AGUNG PROPERTY PALEMBANG) - Rifani Akbar Sulbahri; Indah Permata Sari (Jurnal ACSY : Jurnal Accounting Politeknik Sekayu, 2018)
PT. Indojaya Agung Properti is one of the housing development units (Developers) in the city ofPalembang. Where during its development PT. Indojaya Agung Property must pay taxes determined by theDirectorate General of Taxes. In this connection, this study discusses how the analysis of final PPh collectionon the transfer of rights to land and / or buildings.The results of this study are as follows: First, the applicationof the final PPh on the transfer of rights to land and / or buildings at PT. The Indojaya Agung Property is inaccordance with government regulation number 71 of 2008 concerning payment of income tax from the transferof rights to land and / or other buildings. Both PT. The Indojaya Agung Property using the final PPh rate ismore efficient is Rp. 13,072,500 compared to using article 17 tariff (tarif pasal 17), the amount of tax to be paidis Rp. 32,681,250. greater than using the final PPh rate. Hopefully in the future PT. The Indojaya AgungProperty always applies tax payments in accordance with government regulations in force at that time therebyreducing errors in payment of income tax.Keywords: Final PPh, Final PPh on Transfer of Land and / or Building